Pengembangan E-Book Fisika Dasar Berbasis Pendekatan Saintifik Pada Materi Usaha, Energi, Impuls, dan Momentum. - Nanya Aprillia; Haerul Pathoni; Alrizal Alrizal (Edumaspul: Jurnal Pendidikan, 2021)
This study aims to (1) produce an E-Book based on a scientific approach on the material of Business, Energy, Impulse and Momentum, (2) to find out students' perceptions of E-Book based on a scientific approach on the material of Business, Energy, Impulse and Momentum. This research design uses a 4D research and development design which consists of four stages, namely define, design, develop, and disseminate. The data analysis in this research is descriptive quantitative and qualitative data analysis. From 15 respondents, 66.7% of respondents said that basic physics material is difficult to understand. In the material of Business, Energy, Momentum and Implus, it has a difficulty percentage of 60%. As many as 86.67% of students agree that the scientific approach is suitable for use in the Basic Physics course process